South African women’s bank selection criteria - Mabula, Italia Ramadimetsa (My University, 2013)
This study investigates the bank selection factors of South African women and their order of importance, using Johannesburg as a case study. A quantitative research survey of 115 respondents was used to collect the data needed for this study. The Principal Component Analysis (PCA) method of factor analysis was used to explain the correlations among variables. The main findings of this research are that the most important bank selection factors of South African women include, in order of importance: knowledge and competence of staff (1), speed of service delivery of staff (1), e-banking facilities, i.e. online and mobile banking (2), security and transparency (3), quick, simple and easy to understand processes and services (4), image, attitude and courtesy of staff (5), interest on positive balances (6), bank fees (7), interested charged on loans and overdrafts (8), availability of auto teller machines ATMs (9), suited to my personalized needs (10), rate of interest charged (11), waiting period (12), suited to my household needs (13), ease of access to credit (14), branch accessibility (15), advertising and reward programs (16) and lastly recommendations from family, friends and peers (17), The results of this study suggest that banking and advertising executives who aim to target women more effectively as a segment, not only need to focus on providing great service through capable and competent staff, but also need to do so within an environment that women can trust and in which they feel secure. Women need to feel empowered with simple information that enables them to have a greater understanding of banking products and services, highlighting the financial benefits thereof.
MBA thesis
Keywords: Banks and banking